Will Cape Verde attain COVID‐19 herd immunity? Progress, Challenges, and Recommendations - Deborah Oluwaseun Shomuyiwa; Morolake Ibukunoluwa Otitodun; Tobechukwu Innocentia Anyanwu; Muhsinah Adesewa Abdulwasiu; Alhaji Umar Sow; Maria de Fátima Carvalho‐Alves; Maria da Luz Lima Mendoca; Goodness Ogeyi Odey (Wiley, 2023)
Abstract The COVID‐19 pandemic has exposed the vulnerabilities of Cape Verde's healthcare system, prompting a swift and effective response. This article examines Cape Verde's comprehensive approach to the pandemic, focusing on epidemiology, the healthcare system, and the vaccination campaign. Recognizing the critical role of COVID‐19 vaccination in global efforts, Cape Verde has implemented strategic measures to achieve herd immunity. Although the country has achieved relatively high vaccination coverage in Africa, it still falls short of the necessary threshold. Challenges, including vaccine hesitancy, viral mutations, and supply chain insecurities, must be addressed. Sustained efforts, involving community participation and improved vaccine availability, are crucial. Furthermore, a robust pharmacovigilance system is essential for ensuring vaccination safety and enhancing health outcomes.